Membangun Loyalitas Wisatawan: Peran Citra Destinasi, Kualitas Pelayanan, dan Kepuasan Pengunjung terhadap Minat Kunjungan Ulang di Objek Wisata Kota Semarang - Reynaldi Ade Darmawan; Harmanda Berima Putra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effects of tourist destination image and service standards on the desire to revisit through visitor satisfaction as a mediating variable at tourist attractions in Semarang City. This study uses a quantitative survey-based paradigm. Data was obtained by distributing questionnaires to 166 tourists who had visited tourist attractions in Semarang City using purposive sampling. Data processing was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through the SmartPLS application. The findings of this study indicate that destination perception and service standards have a positive impact on visitor satisfaction. In addition, tourism image, service standards, and visitor satisfaction empirically have a positive effect on the intention to revisit. Mediation effect testing shows that visitor satisfaction successfully bridges the influence of place image and service standards on the intention to revisit. These findings indicate that the formation of a positive destination image and improvement of service standards play an important role in increasing tourist satisfaction and encouraging the intention to revisit. This study is expected to contribute practical recommendations for tourism image managers in designing strategies for sustainable tourism competitiveness development.